An Analytical Study on the Criteria of al-‘Adalah in Hadith Science - Muhammad Abil Endri; Naif Burhan Baisa; Engkos Kosasih; Irwan Abdurrohman; Neni Nurlaela (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The criterion of al-‘adalah is a fundamental requirement in determining the reliability of hadith transmitters, as it directly relates to a person’s moral and religious integrity in narration. However, interpretations of al-‘adalah vary among classical and contemporary scholars. This study aims to critically analyze the concept of al-‘adalah in hadith studies and assess its relevance in modern scholarly contexts. Using a qualitative-descriptive method with content analysis, this research examines classical hadith scholars such as al-Khatib al-Baghdadi and Ibn Hajar al-Asqalani, and compares their views with modern perspectives. The findings reveal that al-‘adalah is shaped not only by personal morality but also by social evaluation and the perception of scholarly communities at the time. The study concludes that the standard of al-‘adalah in hadith science is dynamic and requires reinterpretation to remain relevant in assessing hadith authenticity in the modern era, while allowing room for integration between normative and critical approaches.